Methods for Obtaining Modified Sulfur Bitumen - Sirgievich, Rosilov Mansur; Ro‘ziboyvich, Cho‘liyev Jamshid (Research Parks Publishing LLC, 2024)
Analysis of methods of production of serobitum. Adding the necessary components to the composition of serobitum and obtaining serobitum with a high degree of strength on their basis. They improve the physico-chemical properties of serobitum.